Innovation and competitiveness: An exploratory study on turkish financial sector - (:unkn) unknown (IGI Global, 2014)
While the fostering effect of globalization continues, the traditional perspectives of corporations regarding competition lose their significance as the conventional strategies have started to give way to new approaches in the business world. Many firms have realized the fact that it is fundamentally necessary to revise their competitive strategies to maintain their sustainability. Therefore, "innovation," one of the emerging strategies of competition, has globally become more and more dominant. However, the debate on the strategic value of innovation is still ambiguous not only in the theoretical framework but also in practice. The main purpose of this chapter is to make clear the theoretically informed definition of "innovation" and express its potential for providing competitive advantage in the financial sector. The chapter discusses some of the main scholarly sources of the issues related to the innovation strategies supported by the cases in the Turkish Banking and Insurance Industries. © 2014 by IGI Global. All rights reserved.